Benefit finding moderates the relationship between young carer experiences and mental well-being. Issue 10 (3rd October 2022) - Wepf, Hannah; Joseph, Stephen; Leu, Agnes
Abstract: Objective: Research has shown that some young carers face many negative consequences because of their caring experiences, whereas others seem to be unaffected or even report greater well-being. To understand how caring for a family member or close friend can have these different effects, this study compared benefit finding between young carers and their peers and examined its association with mental well-being. Design: We recruited 2, 525 adolescents aged 15–21 years (59.6% female, M age = 17.73) through the Swiss education system. They were asked to complete measures of caring experiences, benefit finding, and mental well-being. Young carers ( n = 1, 137), including adolescents who currently or formerly provided care, were compared to adolescents without caring experiences ( n = 1, 388). Results: Young carers had a higher level of overall benefit finding than non-carer peers, and their profiles of benefit finding differed regarding the dimensions of growth and empathy. The association between caring experiences and mental well-being was weaker when benefit finding was higher. Benefit finding dimensions were differently associated with mental well-being among young carers. Conclusions: This study shows that caring is associated with benefit finding and suggests that engaging with past stressors in a positive way may promote resilience in young carers.